Quranic survey on the Makkans response to Dakwah - Abdul Ghafar Don; Razaleigh Muhamat @ Kawangit (Penerbit Universiti Kebangsaan Malaysia, 2012)
It is natural that a person who undertakes dakwah responsibility will face challenges and obstacles. The sirah (life)of all messengers withnessed the challenging in doing dakwah. The Prophet Muhammad PBUH. as a chain of Prophets had the same experience as the previous Prophets. This article therefore attempts to explore the Quranic verses as to the Makkans respone to the dakwah during the Prophet Muhammad's time. The method used in this study is based on the documental analysis. which is fully based on the Quranic verses related to the theme. The finding of this study revealed that the Makkan unbelievers extremely negative to the activities of dakwah executed by the prophet Muhammad PBUH.